La realimentación en la evaluación en un curso de laboratorio de Física - Colombo de Cudmani, L.; Pesa de Danón, M.; Salinas de Sandoval, J. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
Methods of continous evaluation with feedback as well as those of discontinuous evaluation without it are discussed. Even though at first sight the former offered advantages upon the latter, and considering their costs in terms of time and effort when working with large groups, it was thought advisable to make a measurement leading to some objective judgement. An experience with students attending a Physics Laboratory Course, 2nd. year Engeneering, was carried out, taking two sample groups and two reference groups, each one constituted by 50 students. After planning and carrying out the experience, results are analized and conclusions drawn which appear to show that the disadvantages implied by continuous evaluation with feedback are largely compensated by the results obtained.